Enhancing Human Resources Competency in a Defense University: Strategies and Best Practices - Setiawan, Bayu (AL-ISHLAH: Jurnal Pendidikan, 2024)
This systematic literature review examines strategies and best practices for enhancing human resources (HR) competencies within defense university environments, focusing on studies published between 2010 and 2023. Recognizing the distinct challenges faced by military educational institutions, the review identifies key themes and methodologies that contribute to effective HR development, including competency alignment with military culture, the integration of advanced training technologies, and leadership development frameworks. A total of 43 articles were analyzed from reputable databases, including Google Scholar, PubMed, Scopus, and Web of Science, with a particular emphasis on research addressing competency frameworks, leadership training programs, and performance evaluation in military contexts. The findings underscore the importance of tailored competency models that adhere to military standards, the adoption of cutting-edge training technologies, and the promotion of continuous professional development. Furthermore, the review highlights successful case studies that demonstrate significant improvements in HR competencies within defense universities. These insights provide a valuable guide for institutions seeking to enhance their HR capabilities. The study concludes by offering recommendations for future research, particularly in exploring innovative competency models, the advancement of training technologies, and leadership development strategies that meet the evolving needs of military organizations.